Analysis of the microbiome: Advantages of whole genome shotgun versus 16S amplicon sequencing - Ranjan, Ravi; Rani, Asha; Metwally, Ahmed; McGee, Halvor S.; Perkins, David L. (Biochemical and biophysical research communications, 2016)
The human microbiome has emerged as a major player in regulating human health and disease. Translational studies of the microbiome have the potential to indicate clinical applications such as fecal transplants and probiotics. However, one major issue is accurate identification of microbes constituting the microbiota. Studies of the microbiome have frequently utilized sequencing of the conserved 16S ribosomal RNA (rRNA) gene. We present a comparative study of an alternative approach using whole genome shotgun sequencing (WGS). In the present study, we analyzed the human fecal microbiome compiling a total of 194.1 × 106 reads from a single sample using multiple sequencing methods and platforms. Specifically, after establishing the reproducibility of our methods with extensive multiplexing, we compared: 1) The 16S rRNA amplicon versus the WGS method, 2) the Illumina HiSeq versus MiSeq platforms, 3) the analysis of reads versus de novo assembled contigs, and 4) the effect of shorter versus longer reads. Our study demonstrates that whole genome shotgun sequencing has multiple advantages compared with the 16S amplicon method including enhanced detection of bacterial species, increased detection of diversity and increased prediction of genes. In addition, increased length, either due to longer reads or the assembly of contigs, improved the accuracy of species detection. •Human microbiome has emerged as a major player in regulating health and disease.•Accurate identification of microbes constituting the microbiome is major challenge.•We report comparative study of whole genome shotgun (WGS) and amplicon sequencing.•WGS enhances detection of bacterial species with high accuracy.•WGS increased detection of microbial diversity and prediction of putative genes.